Efficient anti-radiation treatment agent for magnesium alloy and preparation method of efficient anti-radiation treatment agent

By developing an efficient radiation-proof treatment agent for magnesium alloys containing multiple components, the problem of insufficient electromagnetic shielding effect of magnesium alloys is solved, and the efficient electromagnetic shielding effect at multiple frequencies is achieved, which is suitable for a variety of magnesium alloy grades.

CN119709001APending Publication Date: 2025-03-28HEFEI HUAQING FANGXING SURFACING TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411923446.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

At this stage, the electromagnetic shielding effect of magnesium alloys is mostly below 80dB, especially in high-frequency electromagnetic waves, which is difficult to meet the wider application needs.

Method used

A highly efficient radiation-proof treatment agent for magnesium alloys, including polydimethylsiloxane, graphene oxide, fly ash, magnetic nanoparticles, dispersants, nanocobalt ferrite, rare earth salts and polyaniline, was developed to form a coating through specific mixing and stirring steps to enhance the electromagnetic shielding performance of magnesium alloys.

Benefits of technology

The electromagnetic shielding performance of the treated magnesium alloy at frequencies of 30, 300, 900, 1200, and 1500MHZ is above 90dB, which significantly improves the radiation resistance of magnesium alloys and is suitable for magnesium alloys of different grades.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208623270000031
    Figure BDA0005208623270000031
  • Figure BDA0005208623270000041
    Figure BDA0005208623270000041
  • Figure BDA0005208623270000042
    Figure BDA0005208623270000042
Patent Text Reader

Abstract

The invention relates to the technical field of metal material surface treatment, and discloses an efficient anti-radiation treatment agent for magnesium alloy and a preparation method thereof.The surface treatment agent is prepared from, by weight, 8-15 parts of polydimethylsiloxane, 5-9 parts of graphene oxide, 3-6 parts of fly ash, 2-5 parts of magnetic nanoparticles, 1-3 parts of dispersing agent and 4-8 parts of nano cobalt ferrite. 2-4 parts of rare earth salt, 7-14 parts of polyaniline and 100 parts of absolute ethyl alcohol. In the treating agent, the electromagnetic shielding effect of the magnesium alloy is improved through multiple effects of polydimethylsiloxane, multi-layer graphene oxide, hollow fly ash and magnetic nanoparticles, and the absorption capacity of the magnesium alloy to electromagnetic waves is comprehensively improved by adding nano cobalt ferrite, rare earth salt and polyaniline; the electromagnetic shielding effectiveness of four different brands of magnesium alloys treated by the treatment agent under the frequency of 30-1500MHZ is more than 90dB, and excellent anti-radiation performance is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material surface treatment, and in particular to a high-efficiency radiation protection treatment agent for magnesium alloy and a preparation method thereof. Background Art

[0002] With the rapid development of modern science and technology, various electronic and electrical equipment have brought convenience to human production and life. However, the electromagnetic radiation generated by these electronic and electrical equipment during operation will not only affect the service life of electronic components, cause failures of other electronic instruments, but also endanger human health. In addition, in the development and application of high-tech military products, information security problems caused by electromagnetic radiation interference will have very serious consequences. Therefore, how to reduce electromagnetic radiation has become a focus of increasing attention. At present, there are two main research directions for electromagnetic radiation: one is to develop new radiation-proof materials with high conductivity, light weight, easy processing, environmental protection, corrosion resistance, and good heat dissipation, but the development cycle is long and the cost is high; the other is to improve the radiation-proof effect of existing radiation-proof materials, which is simple to operate and low in cost.

[0003] Magnesium alloy is the metal structural material with the lowest density in engineering applications. It has the advantages of high specific strength, high conductivity, high damping and good cutting performance. In addition, magnesium alloy also has excellent electromagnetic shielding performance, which has obvious advantages in the fields of 3C electronic products, aerospace, etc. However, there are still some problems in using magnesium alloy as radiation protection material. At present, the shielding effect of magnesium alloy is mostly below 80dB, and the shielding effect of high-frequency electromagnetic waves is even worse.

[0004] At present, the research on improving the electromagnetic shielding performance of magnesium alloys and their composites mainly focuses on two aspects: one is the selection of alloying elements and composition design, heat treatment and processing technology, grain size, texture and phase distribution design of magnesium alloys; the other is the surface treatment of magnesium alloys. This method does not need to change the microstructure of the magnesium alloy itself and is simple to operate and easy to implement.

[0005] Based on this, it is of great significance to develop an efficient radiation-proof surface treatment agent for magnesium alloys. Summary of the invention

[0006] In order to improve the radiation protection capability of current magnesium alloys and meet the needs of more application scenarios, the present invention proposes a high-efficiency radiation protection treatment agent for magnesium alloys and a preparation method thereof.

[0007] The technical solution of the present invention is as follows:

[0008] In a first aspect, the present invention discloses a high-efficiency radiation protection treatment agent for magnesium alloy, comprising the following raw materials in parts by weight: 8-15 parts of polydimethylsiloxane, 5-9 parts of graphene oxide, 3-6 parts of fly ash, 2-5 parts of magnetic nanoparticles, 1-3 parts of dispersant, 4-8 parts of nano-cobalt ferrite, 2-4 parts of rare earth salt, 7-14 parts of polyaniline, and 100 parts of anhydrous ethanol;

[0009] Furthermore, the graphene oxide is multi-layer graphene oxide with a sheet diameter of 0.5-5 μm.

[0010] Furthermore, the fly ash is hollow fly ash with a particle size of 8-20 μm.

[0011] Furthermore, the magnetic nanoparticles are one or a mixture of nano-ferroferric oxide with an average particle size of 20 nm or nano-cobalt oxide with an average particle size of 30 nm.

[0012] Furthermore, the dispersant is one of sodium dodecyl sulfonate and sodium dodecyl sulfate, or a mixture of both.

[0013] Furthermore, the particle size of the nano cobalt ferrite is 50-100 nm.

[0014] Furthermore, the rare earth salt is any one of lanthanum nitrate, neodymium nitrate, and cerium nitrate, or a mixture of any two of them.

[0015] Furthermore, the polyaniline is polyaniline doped with dodecylbenzenesulfonic acid.

[0016] In a second aspect, the present invention further discloses a method for preparing the above-mentioned high-efficiency radiation protection treatment agent for magnesium alloy, comprising the following steps:

[0017] Step 1, weigh each raw material by weight;

[0018] Step 2: Add polydimethylsiloxane to anhydrous ethanol, and stir at 300-500 r / min for 1-2 hours at 20-30° C.; then add graphene oxide, fly ash, magnetic nanoparticles and dispersant in sequence, and continue to stir at 700-900 r / min for 2-4 hours after ultrasonic stirring for 40-60 minutes to form a mixture;

[0019] Step 3: Add nano cobalt ferrite, rare earth salt and polyaniline to the mixture, heat to 45-55° C., stir ultrasonically for 30-50 min, and then continue stirring at 700-900 r / min for 4-6 h at 45-55° C. to obtain a high-efficiency radiation protection agent for magnesium alloy.

[0020] The working principle and beneficial effects of the present invention are:

[0021] (1) The high-efficiency radiation protection treatment agent for magnesium alloy of the present invention comprises polydimethylsiloxane, graphene oxide, fly ash, magnetic nanoparticles, dispersant, nano cobalt ferrite, rare earth salt, polyaniline and anhydrous ethanol. The surface treatment agent can form a coating on the surface of magnesium alloy, and the preparation method is simple and suitable for mass production.

[0022] (2) The high-efficiency radiation protection treatment agent for magnesium alloy of the present invention utilizes polydimethylsiloxane as the polymer matrix of the super-hydrophobic surface, thereby blocking certain electromagnetic interference; the graphene oxide with a multi-layer structure and the fly ash with a hollow structure can be used as a reinforcement of the magnesium alloy composite material, causing multi-level electromagnetic reflection inside the magnesium alloy; the magnetic nanoparticles can be used as a physical barrier to make the coating more dense, and the synergistic effect of multiple components can significantly enhance the electromagnetic shielding effect of the treated magnesium alloy.

[0023] (3) The nano cobalt ferrite added to the high-efficiency radiation protection agent for magnesium alloy of the present invention has large magnetic loss characteristics and magnetocrystalline anisotropy, thus having wave absorbing properties; at the same time, the doping of rare earth ions with a unique 4f electron layer structure can further enhance its wave absorbing ability; polyaniline has certain wave absorbing properties while increasing the bonding strength of the coating.

[0024] (4) Four different grades of magnesium alloys were treated with the high-efficiency radiation protection agent for magnesium alloys of the present invention. The electromagnetic shielding effectiveness of the treated magnesium alloys at frequencies of 30, 300, 900, 1200, and 1500 MHZ were all above 90 dB, achieving excellent radiation protection performance. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0027] Example 1

[0028] In this embodiment, the magnesium alloy surface treatment agent is prepared according to the following steps:

[0029] Step 1: Weigh each raw material by weight, as shown in Table 1 below:

[0030] Table 1

[0031]

[0032] Step 2: Add polydimethylsiloxane to anhydrous ethanol, and stir at 400 r / min for 1.5 h at 25° C.; then add graphene oxide, fly ash, magnetic nanoparticles and dispersant in sequence, and continue stirring at 800 r / min for 3 h after ultrasonic stirring for 50 min to form a mixture;

[0033] Step 3: Add nano cobalt ferrite, rare earth salt and polyaniline to the above mixture, heat to 50°C and stir ultrasonically for 40 minutes, then continue stirring at 800r / min at 50°C for 5 hours to obtain a high-efficiency radiation protection agent for magnesium alloy.

[0034] Example 2

[0035] In this embodiment, the magnesium alloy surface treatment agent is prepared according to the following steps:

[0036] Step 1: Weigh each raw material by weight, as shown in Table 2 below:

[0037] Table 2

[0038]

[0039] Step 2: Add polydimethylsiloxane to anhydrous ethanol, and stir at 500 r / min for 2 h at 30° C.; then add graphene oxide, fly ash, magnetic nanoparticles and dispersant in sequence, and continue stirring at 900 r / min for 4 h after ultrasonic stirring for 60 min to form a mixture;

[0040] Step 3: Add nano cobalt ferrite, rare earth salt and polyaniline to the above mixture, heat to 55°C and stir ultrasonically for 50 minutes, then continue stirring at 900 r / min at 55°C for 6 hours to obtain a high-efficiency radiation protection agent for magnesium alloy.

[0041] Example 3

[0042] In this embodiment, the magnesium alloy surface treatment agent is prepared according to the following steps:

[0043] Step 1: Weigh each raw material by weight, as shown in Table 3 below:

[0044] Table 3

[0045]

[0046]

[0047] Step 2: Add polydimethylsiloxane to anhydrous ethanol, and stir at 300 r / min for 1 h at 20° C.; then add graphene oxide, fly ash, magnetic nanoparticles and dispersant in sequence, and continue stirring at 700 r / min for 2 h after ultrasonic stirring for 40 min to form a mixture;

[0048] Step 3: Add nano cobalt ferrite, rare earth salt and polyaniline to the above mixture, heat to 45°C and stir ultrasonically for 30 minutes, then continue stirring at 700 r / min at 45°C for 4 hours to obtain a high-efficiency radiation protection agent for magnesium alloy.

[0049] Example 4

[0050] In this embodiment, the magnesium alloy surface treatment agent is prepared according to the following steps:

[0051] Step 1: Weigh each raw material by weight, as shown in Table 4 below:

[0052] Table 4

[0053]

[0054]

[0055] Step 2: Add polydimethylsiloxane to anhydrous ethanol, and stir at 450 r / min for 1.5 h at 28° C.; then add graphene oxide, fly ash, magnetic nanoparticles and dispersant in sequence, and continue to stir at 850 r / min for 3.5 h after ultrasonic stirring for 55 min to form a mixture;

[0056] Step 3: Add nano cobalt ferrite, rare earth salt and polyaniline to the above mixture, heat to 52°C and stir ultrasonically for 45 minutes, then continue stirring at 850r / min at 52°C for 5.5 hours to obtain a high-efficiency radiation protection agent for magnesium alloy.

[0057] Example 5

[0058] In this embodiment, the magnesium alloy surface treatment agent is prepared according to the following steps:

[0059] Step 1: Weigh each raw material by weight, as shown in Table 5 below:

[0060] Table 5

[0061] raw material Composition and origin Weight Dimethicone Self-purchase 9 Graphene oxide Self-purchased multilayer graphene oxide (sheet diameter 0.5-5μm) 5.5 Fly ash Purchased hollow fly ash (particle size 8-20μm) 3.5 Magnetic Nanoparticles Self-purchased nano-iron tetroxide (average particle size 20nm) 3 Dispersants Sodium dodecyl sulfate 1.6 Nano Cobalt Ferrite Purchased from home (particle size 50-100nm) 5 Rare earth salts Cerium nitrate purchased from 2.5 Polyaniline Dodecylbenzenesulfonic acid-doped polyaniline 8 Anhydrous ethanol Self-purchase 100

[0062] Step 2: Add polydimethylsiloxane to anhydrous ethanol and stir at 350 r / min for 1.5 h at 24° C.; then add graphene oxide, fly ash, magnetic nanoparticles and dispersant in sequence, stir ultrasonically for 45 min, and then continue stirring at 750 r / min for 2.5 h to form a mixture;

[0063] Step 3: Add nano cobalt ferrite, rare earth salt and polyaniline to the above mixture, heat to 48°C and stir ultrasonically for 35 minutes, then continue stirring at 750r / min at 48°C for 4.5 hours to obtain a high-efficiency radiation protection agent for magnesium alloy.

[0064] Comparative Example 1

[0065] The blank control was performed without preparing the high-efficiency radiation protection agent for the surface of magnesium alloy.

[0066] Comparative Example 2

[0067] The preparation method of the magnesium alloy surface treatment agent in this comparative example is different from that in Example 1, the only difference is that polydimethylsiloxane is not prepared in step 1 and polydimethylsiloxane is not added in step 2, and other conditions are exactly the same, and finally a magnesium alloy surface treatment agent is obtained.

[0068] Comparative Example 3

[0069] The preparation method of the magnesium alloy surface treatment agent in this comparative example is compared with that in Example 1, the only difference is that graphene oxide is not prepared in step one and graphene oxide is not added in step two, and other conditions are exactly the same, and finally a magnesium alloy surface treatment agent is obtained.

[0070] Comparative Example 4

[0071] The preparation method of the magnesium alloy surface treatment agent in this comparative example is different from that in Example 1, the only difference is that fly ash is not prepared in step 1 and fly ash is not added in step 2, and other conditions are exactly the same, and finally a magnesium alloy surface treatment agent is obtained.

[0072] Comparative Example 5

[0073] The preparation method of the magnesium alloy surface treatment agent in this comparative example is different from that in Example 1, the magnetic nanoparticles are not prepared in step 1 and the magnetic nanoparticles are not added in step 2. The other conditions are exactly the same, and the magnesium alloy surface treatment agent is finally obtained.

[0074] Comparative Example 6

[0075] The preparation method of the magnesium alloy surface treatment agent in this comparative example is compared with that in Example 1, the only difference is that nano-cobalt ferrite is not prepared in step 1 and nano-cobalt ferrite is not added in step 3, and other conditions are exactly the same, and finally a magnesium alloy surface treatment agent is obtained.

[0076] Comparative Example 7

[0077] The preparation method of the magnesium alloy surface treatment agent in this comparative example is different from that in Example 1, the rare earth salt is not prepared in step 1 and the rare earth salt is not added in step 3. The other conditions are exactly the same, and the magnesium alloy surface treatment agent is finally obtained.

[0078] Comparative Example 8

[0079] The preparation method of the magnesium alloy surface treatment agent in this comparative example is different from that in Example 1, the polyaniline in step 1 and step 3 is replaced by polyvinyl alcohol, and the other conditions are exactly the same, and the magnesium alloy surface treatment agent is finally obtained.

[0080] Comparative Example 9

[0081] The preparation method of the magnesium alloy surface treatment agent in this comparative example is compared with that in Example 1, except that step 2 is removed and "adding to the above mixture" in step 3 is changed to "adding to anhydrous ethanol", and other conditions are exactly the same, and finally a magnesium alloy surface treatment agent is obtained.

[0082] Comparative Example 10

[0083] The preparation method of the magnesium alloy surface treatment agent in this comparative example is different from that in Example 1 in that step 3 is removed, and other conditions are exactly the same, and the mixture prepared in step 2 is directly used as the final magnesium alloy surface treatment agent.

[0084] The magnesium alloy surface treatment agents prepared in Examples 1-5 and Comparative Examples 1-10 were used to perform surface treatment on four commonly used grades of magnesium alloys, namely, AZ31B, AZ91D, AM60B and ZK61M (Comparative Example 1 was not treated). The treatment method was as follows: the magnesium alloy was polished to a bright finish and cleaned with acetone until the surface was clean; then the magnesium alloy sample was immersed in the magnesium alloy surface treatment agent, stirred at 150 r / min for 40 min, then taken out for cleaning with pure water, and then placed in a drying oven at 85°C for curing and drying for 1 h, to obtain the magnesium alloy treated with the surface treatment agent. The performance of the treated magnesium alloy was then tested, and the test method was as follows:

[0085] Shielding effectiveness test: Referring to GB / T 30142-2013 “Measurement method for shielding effectiveness of planar electromagnetic shielding materials”, the samples were tested for electromagnetic shielding effectiveness at frequencies of 30MHZ, 300MHZ, 900MHZ, 1200MHZ and 1500MHZ, and the corresponding shielding effectiveness was recorded.

[0086] The results of the above performance tests are listed in Table 6-7, which is as follows:

[0087] Table 6

[0088]

[0089]

[0090] Table 7

[0091]

[0092] By analyzing the test results in Table 6-7, we can conclude that:

[0093] Examples 1, 2, 3, 4, and 5 are performance test results of four commonly used grades of magnesium alloys, AZ31B, AZ91D, AM60B, and ZK61M, after surface treatment with a high-efficiency radiation protection agent for magnesium alloys prepared under different parameter settings permitted by the present invention. The results show that the high-efficiency radiation protection agent for magnesium alloys prepared by the present invention can be applied to magnesium alloys of different grades, and the electromagnetic shielding effectiveness at 30, 300, 900, 1200, and 1500 MHZ is above 90 dB, achieving high radiation protection performance of the treated magnesium alloy.

[0094] From the comparison of the test results of Comparative Example 1 and Example 1, it can be seen that the high-efficiency radiation protection agent for magnesium alloy prepared in Example 1 can significantly improve the electromagnetic shielding effectiveness of magnesium alloy at different frequencies, and the electromagnetic shielding effectiveness is improved by more than 25dB compared with the untreated magnesium alloy.

[0095] By comparing the test results of Comparative Example 2 with those of Example 1, it can be seen that the polydimethylsiloxane in the high-efficiency radiation protection agent for magnesium alloy prepared in Example 1 can improve the electromagnetic shielding effectiveness of the treated magnesium alloy. This is because polydimethylsiloxane can form a superhydrophobic surface on the magnesium alloy and has good electromagnetic shielding capability.

[0096] By comparing the test results of Comparative Examples 3 and 4 with Example 1, it can be seen that the graphene oxide and fly ash in the high-efficiency radiation protection treatment agent for magnesium alloy prepared in Example 1 can improve the electromagnetic shielding effectiveness of the treated magnesium alloy. This is attributed to the fact that the multi-layered graphene oxide and the hollow structure of the fly ash can serve as reinforcements for the magnesium alloy material, causing multi-level electromagnetic reflections inside the magnesium alloy, thereby improving its electromagnetic shielding effect.

[0097] By comparing the test results of Comparative Example 5 with those of Example 1, it can be seen that the magnetic nanoparticles added to the high-efficiency radiation protection agent for magnesium alloy prepared in Example 1 have a certain positive effect on improving the electromagnetic shielding effectiveness of the magnesium alloy, which is attributed to the fact that the magnetic nanoparticles can act as a physical barrier to make the coating more dense.

[0098] By comparing the test results of Comparative Examples 6 and 7 with Example 1, it can be seen that the nano cobalt ferrite and rare earth salt in the high-efficiency radiation protection treatment agent for magnesium alloy prepared in Example 1 can improve the electromagnetic shielding effectiveness of the treated magnesium alloy. This is because the nano cobalt ferrite has a large magnetic loss characteristic and magnetocrystalline anisotropy, and has high wave absorption performance. At the same time, the unique 4f electron layer structure of rare earth ions is also conducive to improving the wave absorption ability.

[0099] By comparing the test results of Comparative Example 8 with those of Example 1, it can be seen that the addition of polyaniline in the high-efficiency radiation protection agent for magnesium alloy prepared in Example 1 can improve the radiation protection performance of the coating, which is mainly attributed to the wave absorbing property of polyaniline; in addition, polyaniline has a good viscosity effect and can increase the bonding strength of the coating.

[0100] By comparing the test results of Comparative Example 9 with those of Example 1, it can be seen that step 2 in the high-efficiency radiation protection agent for magnesium alloy prepared in Example 1 can significantly improve the radiation protection ability of the treated magnesium alloy. This is because the components of graphene oxide, fly ash, and magnetic nanoparticles all have good shielding capabilities, and their synergistic effect can exert a greater shielding effect on electromagnetic interference.

[0101] By comparing the test results of Comparative Example 10 with those of Example 1, it can be seen that step three in the high-efficiency radiation protection agent for magnesium alloy prepared in Example 1 greatly improves the radiation protection ability of the treated magnesium alloy. This is because the components of nano-cobalt ferrite, rare earth and polyaniline all have certain wave absorption capabilities, and the synergistic effect can further enhance the absorption of electromagnetic waves.

[0102] In summary, the high-efficiency radiation protection treatment agent for magnesium alloy of the present invention can improve the electromagnetic shielding effectiveness of magnesium alloy through the joint action of multiple components, thereby achieving high radiation protection capability.

[0103] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-efficiency radiation protection agent for magnesium alloy, characterized in that: The invention comprises the following raw materials in parts by weight: 8-15 parts of polydimethylsiloxane, 5-9 parts of graphene oxide, 3-6 parts of fly ash, 2-5 parts of magnetic nanoparticles, 1-3 parts of dispersant, 4-8 parts of nano cobalt ferrite, 2-4 parts of rare earth salt, 7-14 parts of polyaniline and 100 parts of anhydrous ethanol.

2. The high-efficiency radiation protection agent for magnesium alloy according to claim 1, characterized in that: The graphene oxide is multi-layer graphene oxide with a sheet diameter of 0.5-5 μm.

3. The high-efficiency radiation protection agent for magnesium alloy according to claim 1, characterized in that: The fly ash is hollow fly ash with a particle size of 8-20 μm.

4. The high-efficiency radiation protection agent for magnesium alloy according to claim 1, characterized in that: The magnetic nanoparticles are one of nano-ferroferric oxide with an average particle size of 20 nm or nano-cobalt oxide with an average particle size of 30 nm, or a mixture of the two.

5. The high-efficiency radiation protection agent for magnesium alloy according to claim 1, characterized in that: The dispersant is sodium dodecyl sulfonate, sodium dodecyl sulfate or a mixture of the two.

6. The high-efficiency radiation protection agent for magnesium alloy according to claim 1, characterized in that: The particle size of the nano cobalt ferrite is 50-100 nm.

7. The high-efficiency radiation protection agent for magnesium alloy according to claim 1, characterized in that: The rare earth salt is any one of lanthanum nitrate, neodymium nitrate and cerium nitrate or a mixture of any two of them.

8. The high-efficiency radiation protection agent for magnesium alloy according to claim 1, characterized in that: The polyaniline is polyaniline doped with dodecylbenzenesulfonic acid.

9. A method for preparing the high-efficiency radiation protection agent for magnesium alloy according to any one of claims 1 to 8, characterized in that: The steps include: Step 1, weigh each raw material by weight; Step 2: Add polydimethylsiloxane to anhydrous ethanol, and stir at 300-500 r / min for 1-2 hours at 20-30° C.; then add graphene oxide, fly ash, magnetic nanoparticles and dispersant in sequence, and continue to stir at 700-900 r / min for 2-4 hours after ultrasonic stirring for 40-60 minutes to form a mixture; Step 3: Add nano cobalt ferrite, rare earth salt and polyaniline to the mixture, heat to 45-55° C., stir ultrasonically for 30-50 min, and then continue stirring at 700-900 r / min for 4-6 h at 45-55° C. to obtain a high-efficiency radiation protection agent for magnesium alloy.

Citation Information

Cited By

  • Polypropylene-based high-voltage cable semi-conductive shielding material, preparation method and cable

    CN121378964A